(untitled) (Journal of Economic Research & Business Administration, 2017)
With the expansion of the circle of users of accounting information on financial and economic activity of the enterprise, the purpose of which is to make profit and competitiveness, significantly increases the interest of participants in the economic process to objective and reliable information about their financial position and business activity. For the economies of most countries are characterized by state regulation and market control methods simultaneously. economic management system includes a variety of functions. One of the most important functions is the account, which provides the system with the necessary information. In this regard, the article discusses the role of accounting information to ensure the development of the world economy.